Answer:
(c) Δ ADE ≅ Δ EBA by AAS Theorem
Explanation:
Here, in Δ ACE
AC = CE (given)
Also, ANGLES OPPOSITE TO EQUAL SIDES ARE EQUAL.
⇒ ∠E = ∠A ..... (1)
Now, in Δ ADE and Δ EBA
∠E = ∠A (from above)
∠ADE = ∠ABC ( right angle)
AE = AE (common side)
hence, Δ ADE ≅ Δ EBA by AAS Theorem
As, by AAS Theorem (ANGLE ANGLE SIDE)
Two triangle said said to be congruent if 2 angles and 1 side of one triangle is equal to 2 corresponding angles and 1 corresponding side of the other triangle.
Hence, Δ ADE ≅ Δ EBA by AAS Theorem